UNDERGRADUATES’ PERCEPTION OF UNETHICAL PRACTICES AMONG LECTURERS IN HIGHER INSTITUTIONS IN DELTA STATE - C. C., Abanobi, (IJRDO- Journal of Educational Research, 2017)
The issue of unethical practices is now the bane of some higher institutions in Nigeria. This study therefore ascertained undergraduates’ perceptions on unethical practices among lecturers in higher institutions in Delta State. Three research questions were raised and answered. Two hypotheses were formulated and tested. The study used a descriptive survey design. The students of Federal College of Education (Technical), Asaba, and Delta State University Abraka, comprised the population of the study. 247 students (112 males and 135 females) were selected across the institutions using convenience sampling technique. The instrument used for data collection was a questionnaire entitled ‘Undergraduates’ Perception of Unethical Practices Questionnaire (UPUPQ)’. The face and content validity of UPUPQ was established by two experts in Measurement and Evaluation. The reliability coefficient of the instrument using Cronbach Alpha method was 0.76. The data collected were analyzed using mean statistics to address the research questions while the hypotheses were tested at .05 level of significance using t-test analysis. The findings revealed that some lecturers in higher institutions engage in unethical practices. Furthermore, factors such as that desperation for promotion, greed for money and many others are causes of unethical practices among lecturers in higher institutions. Also, the difference in the mean perception scores of male and female students on unethical practices among lecturers in higher institutions is not significant. Finally, the difference in the mean perception scores of male and female undergraduates on perceived causes of unethical practices among lecturers in higher institutions is not significant. Based on the findings, the study recommended among others that various higher institutions authority should organize seminar on ethical re-orientation for academic staff in order to combat unethical practices in schools.